Нові місцезнаходження Galanthus nivalis (Аmaryllidaceae) в Українських Карпатах (Закарпатська область) - Москалюк, Б.І.; Діденко, С.Я. (Український ботанічний журнал, 2014)
Приведены данные о трех новых местонахождениях
вида Galanthus nivalis L. в Раховском р-не (Закарпатская
обл.). Описаны условия его местообитаний и состояние
популяций. Исследованы важнейшие демографические
параметры вида в трех популяциях. The data about three new localities of Galanthus nivalis L. in
Rakhiv District (Zakarpatska Region) are reported. The habitats
and populations status for each species are described. The main
demographic parameters of the species within three populations
were studied.